The role of arts in raising ethical awareness and knowledge of the European refugee crisis among social work students. An example from the classroom. Issue 7 (3rd October 2017) - Papouli, Eleni
Abstract: This paper presents and discusses an arts-based project, carried out by the first-year students in the classroom, at the Department of Social Work, in Athens, Greece. The project was designed for raising ethical awareness and knowledge of the 2015 Europe's refugee crisis among social work students. The purpose of this project was three-fold: (1) to help students to better understand the refugee crisis as an emerging problem in Europe and in the rest of the world; (2) to help students raise their ethical awareness about the plight of refugees and to learn how to avoid discrimination and racism; and (3) to improve students' abilities to work effectively with refugee populations. The project used art-based activities (drawing, writing, photos, etc.) as a powerful pedagogical tool for teaching students and supporting their learning in the classroom. As the literature has shown, the use of arts in social work education helps student to learn through an artistic and creative way and provides a secure base, from which they can explore real-life situations and try to give meaning to them.